GIS as a tool for effective preventive conservation. Its utility in studies of conventual outdoor spaces. - Molina Liñán, María Mercedes; López-Bravo, Celia; Ostos-Prieto, Javier (Taylor & Francis, 2019)
The aim of this research is to update conservation methods currently employed for the study of the conventual heritage in Seville. Within these buildings, there are several typologies of open spaces -compasses, courtyards, gardens, orchards and cloisters-, which add complexity to a historical and particularly dense urban layout. Some of these constructions, which undergo the contemporary lack of vocations, have the maximum Spanish heritage recognition as Cultural Assets. A situation that enhances the coexistence of cultural and religious functions in some cases. For these reasons, it is necessary to have a better knowledge about these spaces conservation conditions, specially since they are, sometimes, closed to the public. Consequently, this research proposes the use of Geographic Information Systems as a new way of storage and georeference the pathologies and needs of this buildings on an urban scale. On this matter, priority is given to the visual exploration of the data, reinforcing their spatiality. Then, they can be quantitatively analysed on a territorial scale, not just as isolated buildings. As a result, the aim is to obtain a certain priority order for future interventions and heritage protection of this building typology.
Science and digital technology for cultural heritage: Interdisciplinary approach to diagnosis, vulberability, risk assessment and graphic information models (pp. 94–97)
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/
Keywords: Sistemas de información geográfica; Edificios históricos - Rehabilitación; Patrimonio cultural - Protección; Conventual spaces; Georeferenced system; Heritage protection; Information layers; Preventive conservation